Analisis Faktor-Faktor Yang Memengaruhi Penerimaan Pengguna Dalam Transaksi Online Pada Shopee - Cherly Diansacharina Tri Wahyuningsuara; Retno Indah Rokhmawati; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
This research's goal is to discover what are the factors that affect user acceptance when doing online transactions in Shopee. The criteria of respondents in this research's questionnaire is a user that has done an online transaction using Shopee during the last 6 months. Total sample used in this research is 100 respondent chosen using sampling quota methods. The model used in this research is adapted from Paul Pavlou A.: Actual Transaction, Intention to Transact, Perceived Ease of Use, Trust, and Satisfaction with Past online Transaction. The research started by evaluating the model, Outer Model (Measurement Model) and inner model (Structural model) to find out the data quality and its significant influence towards each variable that has been hypothesized beforehand. The model then evaluated by using PLS-SEM. The result from this research is connection between each factors that affect the user acceptance when doing transaction in Shopee, Intention to Transact affect Actual Transaction, Trust didn't affect Intention to Transact, Perceived Usefulness affect Intention to Transact, Perceived ease of use didn't affect Intention to Transact, Perceived ease of use affect perceived usefulness, perceived risk didn't affect intention to transact, trust affect perceived usefulness, trust affect perceived ease of use, trust affect perceived risk, and satisfaction with past online transaction affect trust.